1997
DOI: 10.1136/fn.77.1.f52
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pattern of 3-oxo-Delta 4 bile acids in neonatal bile acid metabolism

Abstract: Aims-To investigate whether a fetal pathway of bile acid synthesis persists in neonates and infants. Methods-3-oxo-4 bile acids were determined qualitatively and quantitatively in the urine, meconium, and faeces of healthy neonates and infants, using gas chromatography-mass spectrometry. Results-The mean percentage of 3-oxo-4 bile acids in total bile acids in urine at birth was significantly higher than that at 3 or 7 days, and at 1 or 3 months of age. The concentration of this component in meconium was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 17 publications
4
29
1
Order By: Relevance
“…In the fetus and in newborns prior to infancy, 3-oxo-⌬ 4 bile acid intermediate levels are high and similar to the levels observed in the patients (31). However, within the first months of early childhood, these levels dropped significantly, indicating up-regulation of bile acid synthesis and onset of 5␤-reductase activity.…”
Section: Discussionsupporting
confidence: 73%
“…In the fetus and in newborns prior to infancy, 3-oxo-⌬ 4 bile acid intermediate levels are high and similar to the levels observed in the patients (31). However, within the first months of early childhood, these levels dropped significantly, indicating up-regulation of bile acid synthesis and onset of 5␤-reductase activity.…”
Section: Discussionsupporting
confidence: 73%
“…Similar information has been reported by Boehn et al [15]. However, this finding in preterm infants differed from that in full-term infants [1,2,4]. The urinary concentration of total bile acids in the full-term infants increased between birth and 7 days, and gradually decreased thereafter [1,4].…”
Section: Discussionsupporting
confidence: 72%
“…Since 1994, we have studied the developmental pattern of the usual and unusual bile acids, such as unsaturated ketonic bile acids and 1ß-and 7ß-hydroxylated bile acids, in the urine of full-term healthy infants [1][2][3][4]. Several other research groups have reported finding unusual bile acids in the amniotic fluid [5,6], meconium [7,8], umbilical cord blood [5,9] and in the bile from the fetal gallbladder [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This protein has no known function but contains zinc finger domains that may imply a transcription factor activity. 3-Oxo-5-␤-steroid 4-dehydrogenase is necessary in bile acid synthesis (31) and as such may have a role in the hypercholesterolemia that accompanies diabetes. D-Dopachrome tautomerase was downregulated in diabetes and is an inflammatory mediator important in T cell and macrophage migration inhibition (47,63) with no established role in diabetes beyond that ketones are effective inhibitors of this enzyme (19).…”
Section: Ajp-endocrinol Metabmentioning
confidence: 99%